Infusion of Phagocytic Macrophages Overexpressing CPT1a Ameliorates Kidney Fibrosis in the UUO Model - Priscila Calle; Soraya Játiva; Selene Torrico; Angeles Muñoz; Miriam García; Anna Sola; Dolors Serra; Paula Mera; Laura Herrero; Georgina Hotter (Cells, 2021)
Phagocytosis is an inherent function of tissue macrophages for the removal of apoptotic cells and cellular debris during acute and chronic injury; however, the dynamics of this event during fibrosis development is unknown. We aim to prove that during the development of kidney fibrosis in the unilateral ureteral obstruction (UUO) model, there are some populations of macrophage with a reduced ability to phagocytose, and whether the infusion of a population of phagocytic macrophages could reduce fibrosis in the murine model UUO. For this purpose, we have identified the macrophage populations during the development of fibrosis and have characterized their phagocytic ability and their expression of CPT1a. Furthermore, we have evaluated the therapeutic effect of macrophages overexpressing CPT1a with high phagocytic skills. We evidenced that the macrophage population which exhibits high phagocytic ability (F4/80low-CD11b) in fibrotic animals decreases during the progression of fibrosis while the macrophage population with lower phagocytic ability (F4/80high-CD11b) in fibrotic conditions, conversely, increases and CPT1a macrophage cell therapy with a strengthening phagocytic ability is associated with a therapeutic effect on kidney fibrosis. We have developed a therapeutic approach to reduce fibrosis in the UUO model by enrichment of the kidney resident macrophage population with a higher proportion of exogenous phagocytic macrophages overexpressing CPT1a.